2001
DOI: 10.1080/01485010150211155
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Changes in the Calcium Binding Proteins of Mouse Testis

Abstract: To define the changes in calcium-binding proteins (CBPs) of mouse testis during postnatal development, testicular protein extracts were analyzed by mobility shift after Ca2+ binding (MSACB) in the 2-dimensional SDS-PAGE. In the adult testis extracts, 29 kinds of protein spots showed mobility shift in the gel containing Ca2+. Among them, 2 spots showed nonspecific mobility shift and 4 spots showed Zn2+ shift. Drastic changes in expression of high-Mr CBPs (Mr > 25 kDa) were observed in testis 3 weeks after birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This suggests that Ca 2þ homeostasis through the T-type Ca 2þ channel, as well as L-type Ca 2þ channel, is crucial for normal spermatogenesis. During the late stage of spermatogenesis, round spermatids undergo substantial changes in morphology, rearrangements in the composition and function of a number proteins including regulator for the intracellular concentration of Ca 2þ and Ca 2þ -binding proteomes [12,28,30]. Of these, protamines, as well as transition proteins, which are crucial for nuclear remodeling, are expressed in postmeiotic germ cells under control of transcription factor cAMP-responsive element modulator (CREM) [22].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that Ca 2þ homeostasis through the T-type Ca 2þ channel, as well as L-type Ca 2þ channel, is crucial for normal spermatogenesis. During the late stage of spermatogenesis, round spermatids undergo substantial changes in morphology, rearrangements in the composition and function of a number proteins including regulator for the intracellular concentration of Ca 2þ and Ca 2þ -binding proteomes [12,28,30]. Of these, protamines, as well as transition proteins, which are crucial for nuclear remodeling, are expressed in postmeiotic germ cells under control of transcription factor cAMP-responsive element modulator (CREM) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Direct relation of the increase in expression of CREST in pancreatic β-cells of hyperglycemic rats to high glucose-induced apoptosis suggests multifunction of CREST in non-nervous tissues (Men et al 2013). Interestingly, crest mutant mice often develop infertility (Aizawa et al 2004) and a series of proteins interacting with CREST are found closely related to the differentiation and maturation of the spermatogenic epithelial cells (Gye et al 2001;Don and Stelzer 2002;Boussouar et al 2014;Carre et al 2018). Histone acetyltransferases p300 and CREB-binding protein (CBP), two of the earliest identified CREST-interacting proteins, regulate the determination and differentiation of testicular tissues as well as the metabolic remodeling in the later stages of spermatogenesis (Gye et al 2001;Don and Stelzer 2002;Boussouar et al 2014;Carre et al 2018).…”
Section: Introductionmentioning
confidence: 99%